Self-reported adverse events associated with ∆8 -Tetrahydrocannabinol (Delta-8-THC) Use - Eric C. Leas; Raquel M. Harati; Nora Satybaldiyeva; Nicolas E. Morales; Shelby L. Huffaker; Tomas Mejorado; Igor Grant (BMC, 2023)
Abstract Background There is an expanding unregulated market for a psychotropic compound called ∆8-Tetrahydrocannabinol (delta-8-THC) that is being derived from hemp, but a summary of adverse events related to delta-8-THC has not been publicly reported. Methods This case series assessed adverse events reported by delta-8-THC users on the Reddit forum r/Delta8 and compared these to delta-8-THC AEs in the US Food and Drug Administration Adverse Event Reporting System (FAERS). Delta-8-THC and cannabis AEs reported in FAERS were also compared. The r/Delta8 forum was selected because it includes a large sample of 98,700 registered individuals who publicly discuss their experiences using delta-8-THC. All r/Delta8 posts were obtained from August 20, 2020, through September 25, 2022. A random sample of r/Delta8 posts was drawn (n = 10,000) and filtered for posts in which delta-8-THC users reported an adverse event (n = 335). FAERS reports that listed delta-8-THC (N = 326) or cannabis (N = 7076) as a suspect product active ingredient were obtained. Adverse events claimed to result from delta-8-THC use were coded using Medical Dictionary for Regulatory Activities to system organ class and preferred term categories. Results The absolute number of delta-8-THC adverse event reports (N = 2184, 95% CI = 1949-2426) and serious adverse event reports (N = 437; 95% CI = 339-541) on r/Delta 8 were higher than the adverse event reports (N = 326) and serious adverse event reports (N = 289) to FAERS. Psychiatric disorders were the most frequently cited system organ class in r/Delta8 adverse event reports, mentioned in 41.2% (95% CI = 35.8%-46.3%) of reports, followed by respiratory, thoracic and mediastinal disorders (29.3%, 95% CI = 25.1%-34.0%) and nervous system disorders (23.3%, 95% CI = 18.5%-27.5%). Anxiety (16.4%, 95% CI = 12.8-20.6), Cough (15.5%, 95% CI = 11.9-20.0) and Paranoia (9.3%, 95% CI = 6.3-12.5) were the most frequently cited preferred terms in adverse event reports. The overall prevalence of AEs reported for cannabis and delta-8-THC on FAERS were also similar when analyzed by system organ class (Pearson's r = 0.88). Conclusions The findings of this case series suggest that most of the adverse events reported by delta-8-THC users are like those reported during acute cannabis intoxication. This finding suggests that health care professionals follow similar treatment and management protocols, and that jurisdictions should clarify whether delta-8-THC can be sold as a hemp product.